Atopic Dermatitis or Hyper IgE Syndrome? - Ahmed, M; Kumar, A; Raj, D (Journal of Nepal Paediatric Society, 2015)
Eczema and skin infections are commonly encountered in children in the outpatient department. However, presence of both recurrent dermatitis and skin infections should alarm one to consider Hyper IgE syndrome (HIES) as a differential. Here we present a case of HIES in a two and a half year old female child with history of recurrent dermatitis and skin infections in the form of cold abscesses. Laboratory investigations showed markedly elevated IgE levels and high absolute eosinophils counts. Patient was treated with trimethoprim-sulfamethoxazole and supportive care. The current report highlights the fact that HIES can present in early childhood with just skin manifestations and without any significant pulmonary manifestations. J Nepal Paediatr Soc 2015;35(1):59-61